Pengujian Life Cycle Model of Dividends Sektor Perbankan di Bursa Efek Indonesia - Muhamad Umar Mai (Jurusan Akuntansi Politeknik Negeri Malang, 2022)
This study examines the Life Cycle Model of Dividends (LCMD) of the banking sector on the Indonesia Stock Exchange (IDX) during the period 2005-2020. This study uses secondary data which was analyzed by logistic regression. The results of this study indicate that the dividend policy of the bank sector on the IDX tends to follow the LCMD. Another important result is that the Capital Adequacy Ratio, which is not a proxy for the LCMD variable, also shows an important role in determining dividend policy for the bank sector on the IDX. Abstrak Penelitian ini menguji Life Cycle Model of Dividends (LCMD) sektor perbankan di Bursa Efek Indonesia (BEI) selama periode 2005-2020. Penelitian ini menggunakan data sekunder yang dianalisis dengan regresi logistik. Hasil penelitian ini mengindikasikan bahwa kebijakan dividen sektor bank di BEI cenderung mengikuti LCMD. Hasil penting lainnya adalah bahwa Capital Adequacy Ratio, yang bukan merupakan proksi variabel LCMD, juga menunjukkan peranan yang penting dalam menentukan kebijakan dividen bagi sektor bank di BEI.